2018
DOI: 10.1038/s41588-018-0222-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of blood lipids among ~300,000 multi-ethnic participants of the Million Veteran Program

Abstract: The Million Veteran Program (MVP) was established in 2011 as a national research initiative to determine how genetic variation influences the health of U.S. military veterans. We genotyped 312,571 MVP participants using a custom biobank array and linked the genetic data to laboratory and clinical phenotypes extracted from electronic health records covering a median of 10.0 years of follow-up. Among 297,626 veterans with at least 1 blood lipid measurement including 57,332 blacks and 24,743 Hispanics, we tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
559
2
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 552 publications
(593 citation statements)
references
References 60 publications
28
559
2
4
Order By: Relevance
“…Lipids GWAS summary statistics were obtained from the Million Veteran Program (MVP) (up to 215,551 European individuals) 20 and the Global Lipids Genetics Consortium (GLGC) (up to 188,577 genotyped individuals). 12 As additional exposures in multivariable MR analyses, we used BMI summary statistics from a meta-analysis of GWAS in up to 795,640 individuals, and age at menarche summary statistics from a meta-analysis of GWAS in up to 329,345 women of European ancestry.…”
Section: Study Populationsmentioning
confidence: 99%
“…Lipids GWAS summary statistics were obtained from the Million Veteran Program (MVP) (up to 215,551 European individuals) 20 and the Global Lipids Genetics Consortium (GLGC) (up to 188,577 genotyped individuals). 12 As additional exposures in multivariable MR analyses, we used BMI summary statistics from a meta-analysis of GWAS in up to 795,640 individuals, and age at menarche summary statistics from a meta-analysis of GWAS in up to 329,345 women of European ancestry.…”
Section: Study Populationsmentioning
confidence: 99%
“…A customized Affymetrix Axiom Biobank array, with 723,305 SNPs, was used for high‐throughput genotyping. Details of sample and variant quality control are described elsewhere (Klarin et al, ). Briefly, duplicate samples, samples with more heterozygosity than expected, an excess (>2.5%) of missing genotype calls, or discordance between genetically inferred sex and phenotypic gender were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…SNPs, was used for high-throughput genotyping. Details of sample and variant quality control are described elsewhere (Klarin et al, 2018).…”
Section: Genotyping and Imputationmentioning
confidence: 99%
“…The establishment of The Million Veterans Program (MVP), a large-scale biobank within the Veterans Health Administration (VHA), one of the largest integrated health systems in the United States, provides the ability to evaluate longitudinal health data with pharmacy prescription data, and will enable discovery of genetic markers underlying disease risk and drug response. 6,7 The VHA population also includes a significant number of black and Hispanic ancestry individuals, which will drive discovery of new drug targets, facilitate identification of causal genetic variants, and help reveal genetic heterogeneity in drug-related traits. For example, a multiethnic genome-wide association study of blood lipid levels in MVP participants identified novel rare coding variants in PCSK9, LDLR, APOB, and ABCA1 that were specific to black or Hispanic individuals.…”
Section: Informatics Serves As the Bridge Linking Clinical Practice Amentioning
confidence: 99%
“…For example, a multiethnic genome-wide association study of blood lipid levels in MVP participants identified novel rare coding variants in PCSK9, LDLR, APOB, and ABCA1 that were specific to black or Hispanic individuals. 7 Previous work identifying low-frequency missense variants has led to the development of novel classes of therapeutics to treat cardiovascular disease (e.g., PCSK9 inhibitors). More sophisticated informatics methods that can automate extraction of research-quality drug response phenotypes are being developed by MVP investigators and others to aid in the discovery of new targets and drug effects, and in patient management.…”
Section: Informatics Serves As the Bridge Linking Clinical Practice Amentioning
confidence: 99%